2021
DOI: 10.1017/ice.2021.165
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the excess bed days and economic burden of healthcare-associated infections in Singapore public acute-care hospitals

Abstract: We estimated the annual bed days lost and economic burden of healthcare-associated infections to Singapore hospitals using Monte Carlo simulation. The mean (standard deviation) cost of a single healthcare-associated infection was S$1,809 (S$440) [or US$1,362 (US$331)]. This translated to annual lost bed days and economic burden of 55,978 (20,506) days and S$152.0 million (S$37.1 million) [or US$114.4 million (US$27.9 million)], respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 9 publications
(10 reference statements)
0
6
0
Order By: Relevance
“…The quality of the data used for the model parameters is good, with the data gathered for the first national prevalence survey [14] utilised for this analysis. The excess length of stay parameters were estimated using a state-based model that appropriately includes the timing of key events of HAI, death and discharge from hospital [20]. A recent review found analyses that use time fixed methods for the estimation of these outcomes generate biased, inflated, outcomes [28].…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the data used for the model parameters is good, with the data gathered for the first national prevalence survey [14] utilised for this analysis. The excess length of stay parameters were estimated using a state-based model that appropriately includes the timing of key events of HAI, death and discharge from hospital [20]. A recent review found analyses that use time fixed methods for the estimation of these outcomes generate biased, inflated, outcomes [28].…”
Section: Discussionmentioning
confidence: 99%
“…In the study, patients with CRE and CSE HAIs were indirectly matched for time at risk by matching to a common control group without infection. Estimates for annual CRE HAI incidence were based on studies published by Cai et al [11,12]. Drug doses followed international antibiotic guidelines [13].…”
Section: Data Inputmentioning
confidence: 99%
“…It was previously estimated that the incidence of HAIs among patients admitted in public acute care hospitals in Singapore was 15,980 ± 840 patients per 100,000 inpatient admissions [12]. Based on the Singapore point prevalence survey on HAIs, 151 out of 727 HAIs (20.8%) were attributable to Enterobacterales; of these, 7.0% were non-susceptible to carbapenems (% of CRE HAIs out of all HAIs = 1.5%) [11].…”
Section: Expected Annual Burden Of Cre Haismentioning
confidence: 99%
See 1 more Smart Citation
“…PCNSIs are associated with significantly increased treatment costs, prolonged hospitalization time, psychological trauma, and delayed postoperative adjuvant treatment. These factors can place a substantial economic and psychological burden on society and patients’ families ( 5 ).…”
Section: Introductionmentioning
confidence: 99%